DEVELOPMENT OF NATIONAL VALUES IN STUDENTS DISTINCTIVE FEATURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article talks about the benefits of forming national values in students. Values are the basis of the development of society, a powerful factor that transfers the achievements of the nation in its historical development from generation to generation. Looking at the stages of historical development, not every society, state has advanced without developing and strengthening its national values